Effects of adding betaine on laying performance and contents of serum yolk precursors VLDL and VTG in laying hen - LU Jian-jun; ZOU Xiao-ting (浙江大学学报. 农业与生命科学版, 2006)
Eight hundred ISA laying hens of 20 weeks of age were tested to investigate the effects of betaine on contents of serum yolk precursors VLDL (very low-density lipoprotein) and VTG (vitellogenin) for 350 days. Laying hens were randomly allotted to four groups with four replicates each. The groups were fed a corn-soybean basal diet, supplemented with 0, 400, 600, 800 mg·kg-1 betaine. It indicated that addition of 600 mg·kg-1 betaine significantly improved egg production by 8.67% (P< 0.05) compared with control. Supplementation of 600 mg·kg-1 betaine increased concentration of VLDL by 34.61% (P<0.05) and 53.41% (P<0.03); VTG by 33.74% (P<0.01) and 39.14% (P<0.01), decreased activity of LPL in abdominal fat by 31.0% (P<0.01) and 44.83% (P<0.01) in 50 and 70-week old laying hens respectively. It indicates that the contents of serum yolk precursors VLDL and VTG were significantly affected by betaine in laying hen.